(5x+6)=(3x+7)

Simple and best practice solution for (5x+6)=(3x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x+6)=(3x+7) equation:



(5x+6)=(3x+7)
We move all terms to the left:
(5x+6)-((3x+7))=0
We get rid of parentheses
5x-((3x+7))+6=0
We calculate terms in parentheses: -((3x+7)), so:
(3x+7)
We get rid of parentheses
3x+7
Back to the equation:
-(3x+7)
We get rid of parentheses
5x-3x-7+6=0
We add all the numbers together, and all the variables
2x-1=0
We move all terms containing x to the left, all other terms to the right
2x=1
x=1/2
x=1/2

See similar equations:

| 4(1-8x)=29-7x | | 2x=27=2x-11 | | 32.00+9.25x+15.00=124.25 | | 2x-(-11)=12 | | 9(3a-7)=-2a-15-4a | | 6y–1=2(3–y) | | 7x-1+11x-29=180 | | 6x+155=445 | | -4(y+6)+y=9 | | 7+3(6x+3)=52 | | 14x+15=192 | | 6a^2+14-5a=0 | | 5(e+6=75 | | 8x4=23-11 | | 27=7(x)+6 | | 3(x–7)+4=28–2x | | a−37=2/7 | | 8x2+20x+12=0 | | a−3/7=2/7 | | 2(x-4)+3=13-4x | | x^2-5x+43=57 | | -4s+8s+2=125 | | p=31/6=-21/2 | | −1+a=-6 | | 12+37x=−15 | | 40=3.10x+5.00 | | -15x-5=10x+25 | | y+1/2=2/3 | | 138+27x=47+40x | | x-177x+5=180 | | 3z+5(z-5)=-48 | | 12x+5=3(4x-5) |

Equations solver categories